(untitled) - Heck, Joseph (Indianapolis, IN, 1996)
This follow-up to the bestselling Using Netscape provides detailed coverage of Netscape 2 for Macintosh, including support for Java, new integrated e-mail and newsreading features, new support for online purchases with digital IDs, and more. It also offers information about special HTML editing tools in Netscape Navigator 2 Gold.
Keywords: World Wide Web,Mạng diện rộng